Physicochemical properties and water quality parameter of paddy soil and water and their relationship with pesticides concentration - Zaidon, Siti Zulfa; Ho, Yu Bin; Hashim, Zailina; Saari, Nazamid; Praveena, Sarva Mangala (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Pesticides may influence the physicochemical properties of soil and the water quality parameters, which is vital in maintaining soil fertility and producing high quality crops. Objective: This study aims to determine the relationship between the concentration of pesticides, the physicochemical properties of the paddy soil samples and the water quality parameters of paddy water samples. Methods: A total of 72 soil and 72 water samples were collected in Tanjung Karang, Malaysia. The paddy soil and water were extracted using Quick, Easy, Cheap, Efficient, Rugged and Safe (QuEChERS) and solid phase extraction (SPE) techniques respectively. The concentrations of pesticides were analysed in ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS). The relationship of the concentration of target pesticides and the paddy soil and water physicochemical properties were studied using Spearman correlation. Results: In paddy soil, the concentration of propiconazole shows moderate positive correlation with manganese (Mn) (r = 0.587) (p≤ 0.01). Meanwhile buprofezin-total organic carbon (TOC) (r = -0.55) (p≤ 0.01), imidacloprid-cation exchange capacity (CEC) (r = -0.519) (p≤ 0.01), pymetrozine-sodium (Na) (r = -0.588) (p≤ 0.01), and trifloxystrobin-calcium (Ca) (r = 0.566) (p≤ 0.01) showed moderate negative correlation. Whereas in water, trifloxystrobin showed significant positive correlation with turbidity (r = 0.718) (p≤ 0.01) and tebuconazole showed negative correlation to dissolved oxygen (DO) (r = 0.634) (p≤ 0.01). Conclusion: The presence of pesticides in paddy field may influence the soil and water quality, thus regular monitoring of pesticides usage and nutrient management in soil is deemed important.